2009
DOI: 10.1021/jp901162s
|View full text |Cite
|
Sign up to set email alerts
|

Water Adsorption at a Sodium Smectite Clay Surface: an Ab Initio Study of the First Stage

Abstract: Using calculations based on density-functional theory, we explore the configurations that water molecules (2,3,4;6) assume on the surface a sodium 2:1 smectite clay with isomorphic substitutions both on octahedral and tetrahedral sheets. The hydrophilicity of the surface is inhomogeneous, depending on the specific location of the counterions and of the cation replacements in the siloxane rings. The counterion does not complete the first hydration shell. Adsorption may occur in the form of coexisting monomers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 22 publications
6
15
0
Order By: Relevance
“…For hydrated systems with a sodium cation, it has been shown that water adsorbs most preferably via a hydrogen bond to one of the surface oxygen atoms while oriented by its oxygen atom toward Na + . 47 These findings agree with our results for small kaolinite models. Thus, such initial structures of water and Na + placed close to FA on the kaolinite surface were applied in calculations presented in this paper.…”
Section: Models and Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…For hydrated systems with a sodium cation, it has been shown that water adsorbs most preferably via a hydrogen bond to one of the surface oxygen atoms while oriented by its oxygen atom toward Na + . 47 These findings agree with our results for small kaolinite models. Thus, such initial structures of water and Na + placed close to FA on the kaolinite surface were applied in calculations presented in this paper.…”
Section: Models and Methodssupporting
confidence: 92%
“…In the presence of a sufficient amount of Na + , the surface charge of the mineral can be neutralized, making negatively charged mineral surfaces good adsorbents. 45 The cation's nearest environment contains one magnesium substitution in the octahedral sheet 46,47 or one aluminum substitution in the tetrahedral sheet. 48 Thus, in our study after substitution in the sheets, the model was kept electroneutral by the addition of a sodium cation (one of the most common exchangeable cations of kaolinite 26 ), which compensated a single (1−) negative surface charge.…”
Section: Models and Methodsmentioning
confidence: 99%
“…The cations within the interlayer space have the ability to hydrate [Norrish, 1954], resulting in continuous sheets of hydrogen-bonded water molecules that decrease tetrahedral layer contact area and reduce shear strength [Schleicher et al, 2013;Behnsen and Faulkner, 2013]. Furthermore, smectites can adsorb multiple (two to six) monolayers of water to their surface [Clausen et al, 2009]. Thus, the effect of water in smectite friction is strongly related both to adsorbed water on the mineral surface [Moore and Lockner, 2004] and to bound water in the interlayer.…”
Section: Strength Results and Effects Of Water Distributionmentioning
confidence: 99%
“…V. Aggarwal et al have investigated adsorption of polar organic compounds onto montmorillonite. P. Clausen et al have computed the adsorption of volatile molecules . To the best of our knowledge, no theoretical studies focusing on the interaction between atrazine and clays have been performed.…”
Section: Introductionmentioning
confidence: 99%